Dos provimentos vinculantes aos casos sob julgamento: uma análise empírica sobre a (in)observância do art. 489, § 1º, V, do CPC/2015, nos acórdãos do STJ (2016-2019). - Araújo, Tiago Cisneiros Barbosa de (2020)
Does the Brazilian Superior Court of Justice (STJ) compare ratio decidendi of binding judicial provisions with the circumstances of the cases under trial, as established in Article 489, §1º, V, of Civil Procedure Code (CPC /2015)? The question that guides this work is related to the system of binding provisions - or “precedents”, a term that has been used as a genre for the types of pronouncements listed in Article 927, of the same code. It is also related to the judicial duty of reasoning, contained in the Brazilian Constitution of 1988 and reinforced by CPC. It is adopted a provisional negative response to the research problem, that is, STJ does not obey the rule contained in that statute. To explore the issue, this work is built on a mixed methodological perspective. The dogmatic approach predominates in the first four chapters and an empirical and quantitative analysis, of an exploratory and descriptive nature, in the fifth. Review of legal literature and national and foreign doctrine is used, in addition to the critical analysis of the performance of the Judiciary. One the themes discussed in the first chapter are the similarities and differences between the Brazilian system and the Common Law models that inspired it, as well as the possibilities and limits of legal transplants. In the second and third chapters, there is an approach about the content and the ways of identifying ratione decidendi, in the foreign doctrine of stare decisis and also in Brazilian system. In the fourth chapter, it deals with the judicial duty to give reasons, also seen as a right, and its repercussions on the rights of prior hearing, impartiality, equality, etc. In addition, motivation techniques with precedents or binding provisions are discussed, such as distinction, overruling and its variables and distortions. In the fifth and last chapter, the empirical-quantitative approach is deepened, with analysis and classification of a sample of 384 collective decisions, published by the first four court classes, during the first three years of the CPC/2015, in order to respond the research question and other issues, such as association between the use of binding provisions and the judgments’ results. Logistic regression technique (logit) is used for this purpose. Besides that, it’s developed a reasoning quality index for the 219 opinions that used binding provisions as decisionmaking grounds. They receive scores from 1 until 101. Among the main research conclusions, there is the fact that Brazin has its own system of judicial binding provisions, with relevant similarities and divergences in comparison to Common Law models, from which it is distanced by normative aspect and also by legal practice, marked by low argumentative effort and by the attachment to ‘theses’ and statements. Due to the empirical-quantitative research, the negative hypothesis is confirmed, since only three of the 219 decisions obey Article 489, §1º, V, of the CPC. In the quality index, most of the opinions (158 out of 219) scored lower than the average, with 59 of them being awarded 1 to 11 points, due to the absence or deficiency of identification of the relation between the binding provision used and the case under judgment.